PENGARUH KUALITAS SDM DAN SISTEM AKUNTANSI TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DESA - Rieka Ramadhaniyah; Ridho Muhamat Arif (Bajang Institute, 2022)
This study aims to determine the effect of the quality of human resources and accounting systems on village financial management accountability. Respondents for this research were the Rajabasa Lama 1 Village and Apparatus Organization, Labuhan Ratu, East Lampung. sample data collection was taken based on non-probability sampling with a purposive sampling system. The results of the quality of human resources have a significant effect on village financial accountability. Village apparatus has a significant effect on village financial accountability. The village accounting system has a significant effect on village financial accountability.